Integrasi Edukasi Infused Water dan Pemilahan Sampah: Model Pengabdian Masyarakat untuk Peningkatan Pengetahuan, Keterampilan, dan Kualitas Hidup. - Irsanty Collein; Ismunandar Ismunandar; Fitria Masulili (Poltekita: Jurnal Pengabdian Masyarakat, 2026)
Hypertension and household waste management are significant issues faced by Indonesian communities, particularly in Wombo Kalonggo Village.  Most villagers work as farmers, while many women remain at home, and the availability of large land areas has contributed to improper waste management practices. Waste is often discarded into dry rivers or openly burned in household yards. This community service program aimed to enhance integrative community knowledge through education on infused water preparation as an effort to prevent hypertension and education on sorting organic and inorganic waste as an environmental management strategy. The method applied was a participatory approach, involving the community in socialization, hands-on practice, and interactive discussions. Infused water education proved effective in improving community knowledge and awareness of healthy lifestyles, particularly in hypertension prevention. Meanwhile, waste sorting education enhanced villagers’ skills in managing household waste and fostered environmentally friendly behavior. The integration of these two programs created a holistic approach that focused not only on individual health but also on environmental cleanliness. The outcomes of this program showed a significant improvement in knowledge, skills, and awareness among the community after the intervention. This initiative highlights the importance of integrating health and environmental education into a sustainable community service program.